Innovative Research in the Food Packaging to Improve Food Quality and Shelf Life - Rizzo, Valeria; Muratore, Giuseppe (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Food packaging and shelf life have been the subject of remarkable research in recent years. They are so important because only by understanding a good storage system is it possible to avoid any food waste. Moreover, the best packaging has to prolong the food quality while also reducing the packaging volume or better, become itself biodegradable, and guarantee the nutritional characteristics of food products.In particular, the increasing interest in reducing packaging wastes is becoming a rising problem, just considering that food packaging alone contributes to a huge portion of total packaging wastes in the world. On the other side, consumers judge the food quality based on appearance and freshness, but also using their awareness of the environmental implications of packaging. Nowadays, many technologies can be applied to improve food quality and shelf life, such the application of edible films or coatings, from biodegradable materials or biopolymers, trying to reduce the package barrier requirements, incorporating natural bioactive compounds and lengthening shelf life making then packaging easily compostable.